“If You Could Die…”: Hart Crane’s “Accursed Share” in Mexico - Beatrice Pire (European Journal of American Studies)
This article explores the “spirit of sacrifice” and the influence of Aztec religion, as analyzed by Georges Bataille in various writings, on two poems written by Hart Crane in Mexico shortly before his suicide.